2021
DOI: 10.1038/s41467-021-23449-6
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular three-dimensional imaging deep through multicellular thick samples by structured illumination microscopy and adaptive optics

Abstract: Structured Illumination Microscopy enables live imaging with sub-diffraction resolution. Unfortunately, optical aberrations can lead to loss of resolution and artifacts in Structured Illumination Microscopy rendering the technique unusable in samples thicker than a single cell. Here we report on the combination of Adaptive Optics and Structured Illumination Microscopy enabling imaging with 150 nm lateral and 570 nm axial resolution at a depth of 80 µm through Caenorhabditis elegans. We demonstrate that Adaptiv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The imaging can be done up to 20 µm into a sample, but the resolution is decreasing with increasing depth of imaging ( Heintzmann and Huser, 2017 ; Bartle et al, 2018 ; Wu and Shroff, 2018 ; Gonschior et al, 2020 ; Bond et al, 2022 ). Recent developments applying adaptive optics ( Ji 2017 ) with SIM enable imaging with 150 nm lateral and 570 nm axial resolution at a depth of 80 µm through the C. elegans ( Lin et al, 2021 ). One of the advantages of SIM is that it is a relatively simple and straightforward optical setup.…”
Section: Light-based Microscopy Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…The imaging can be done up to 20 µm into a sample, but the resolution is decreasing with increasing depth of imaging ( Heintzmann and Huser, 2017 ; Bartle et al, 2018 ; Wu and Shroff, 2018 ; Gonschior et al, 2020 ; Bond et al, 2022 ). Recent developments applying adaptive optics ( Ji 2017 ) with SIM enable imaging with 150 nm lateral and 570 nm axial resolution at a depth of 80 µm through the C. elegans ( Lin et al, 2021 ). One of the advantages of SIM is that it is a relatively simple and straightforward optical setup.…”
Section: Light-based Microscopy Techniquesmentioning
confidence: 99%
“…Tissue clearing gives the opportunity to image with reduced light scattering and increased imaging depth with a range of microscopic and tomographic methodologies of larger and thicker samples ( Almagro et al, 2021 ). Developments in the optics aspect of microscopy enabled researchers to image, with SIM, samples thicker than a single cell ( Lin et al, 2021 ). This could be promising to image junctions in tissues instead of cell cultures with super-resolution microscopy.…”
Section: How To Choose the Right Imaging Technique For Your Intercell...mentioning
confidence: 99%
“… Direct wavefront sensing High sensing speed / Require wavefront sensors, Need fluorescent labeling, weak at scattering Oligodendrocytes and neuronal nuclei in a zebrafish brain in vivo [ 33 ] Neurons in a Thy1-YFPH mouse brain in vivo [ 34 ] mRuby2-labeled layer 5 pyramidal neurons of vS1 mouse brain cortex in vivo [ 35 ] A live human stem cell-derived organoid [ 36 ] The eye of a zebrafish embryo 24 hpf. [ 36 ] Cortical neurons of a Thy1-GFP mouse brain in vivo [ 37 ] C. elegans in vivo expressed by the adherens junction marker ajm-1::GFP [ 38 ] Indirect wavefront sensing Better suited to opaque tissues than direct wavefront sensing, Require no wavefront sensors / Slow sensing speed due to hardware feedback, Deal with low-order aberrations modes, Need fluorescent labeling The visual cortex and Hippocampus of mouse brain in vivo [ 39 ] Synaptic structures in the deep cortical region of a Thy1-GFP mouse brain [ 40 ] High and basal dendritic spines of a mouse V1 neuron in vivo [ 41 ] GFP expressed microtubule of Drosophila larval macrophage [ 42 ] GFP-expressed pyramidal neuron in a living mouse brain [ 43 ] Single microglia cell from hippocampus tissue of a mouse brain [ 44 ] Coherence-gating Label-free, High sensing speed / Mixed phase retardations of input and output paths, Deal with low-order aberration modes Olfactory bulb in transgenic zebrafish larvae [ 45 ] Time-gated reflection matrix Label-free, Better suited to opaque tissues, Numerical post-processing, Seperation of input and output aberrations, High- order aberration correction / Matrix acqusition time depending on scattering Hyphae of Aspergillus cells in a rabbit’s cornea [ ...…”
Section: Technical Improvement For Deep-tissue Imaging Based On Adapt...mentioning
confidence: 99%
“…Another study reported that the method of widefield illumination, structured illumination, and confocal illumination was integrated into one system with AO, in which AO can be applied to direct or indirect wavefront sensing by simply changing the optical path [ 38 ]. This study implemented the all-in-one system combined with the image-based sensorless wavefront sensing, confocal sensorless adaptive optics, and direct wavefront sensing, thereby, developed the three-dimensional SIM.…”
Section: Technical Improvement For Deep-tissue Imaging Based On Adapt...mentioning
confidence: 99%
“…An advantage of SIM technology is the use of digital cameras for detection, rather than single point detectors, enabling these microscopes to capture highly dynamic events at frame rates exceeding 100+ frames per second [ 29 ]. Although SIM has minimal phototoxicity effects, it is limited by light penetration to maximal depths of ~200 μm [ 30 , 31 ].…”
Section: Fluorescence Microscope Hardware Systemsmentioning
confidence: 99%